(untitled) (Bangladesh Critical Care Journal, 2019)
Hydroxyurea is an antineoplastic agent used to treat chronic myeloid leukaemia (especially in accelerated phaseand blast crisis). We report this unique case of a 60 year old lady who was diagnosed case of chronic-phase ofchronic myeloid leukaemia was getting imatinib and well suited. As a consequence of imatinib noncompliance,she developed blast crisis and was subsequently hydroxyurea initiated. At her 3rdmonth follow-up she presentedwith blackening of her exposed parts of the body, all three mucocutaneous areas especially skin of her hands, feet,fingernails, toenails and oral mucosa in some extent.Hydroxyurea-induced melanonychia and mucocutaneous hyperpigmentation is rarely reported. To the best of ourknowledge, this is one of the few published reports of hydroxyurea induced mucocutaneous hyperpigmentationand melanonychia involving all 20 nails. The mainstays of treatment are withdrawal of the drug andsun-avoidance; laser therapy is a hope for cure in small percentage of permanent cases. A correct diagnosis isessential to prevent undue fears in the patient. Proper advice to the patient regarding adverse reactions ofparticular agent and close monitoring after prescribing should be ensured to prevent harm to patients. Alwaysshould remember, drugs not only save life, but can even take it. Bangladesh Crit Care J September 2019; 7(2): 106-108